Sleep complaints and sleep breathing disorders in upper and lower obstructive lung diseases - Ferrando, Matteo; Bagnasco, Diego; Roustan, Valeria; Canonica, Giorgio Walter; Braido, Fulvio; Baiardini, Ilaria (Journal of Thoracic Disease, 2016)
Upper and lower obstructive lung diseases can induce sleep complaints and can be part of the pathogenesis of sleep breathing disorders. In fact, the physiological changes of the pattern of respiration during sleep, added to the airways disease can lead to symptomatic worsening of rhinitis, asthma and chronic obstructive pulmonary diseases (COPD); moreover, their functional and anatomical features can lead to sleep breathing disorders such as obstructive sleep apnea syndrome (OSAS). This review highlights the above-mentioned relationships and the effect of disease management on its comorbidities and the patient’s quality of life. Rhinitis, asthma and COPD represent causes of sleep complaints that may be reduced with optimal management of these obstructive airways diseases. Continuous positive airway pressure (CPAP) treatment of sleep apnea needs to be tailored after optimization of the therapy of concomitant diseases, but it can often ameliorate comorbid disease.